Land Use Land Cover Dynamics of Ise Forest Reserve, Nigeria (e-Proceedings of the Faculty of Agriculture International Conference, 2024)
Understanding the dynamics of Land Use Land Cover (LULC) is necessary for generating valuable information for informed decision-making in managing natural resources in the tropics. However, relevant information on these dynamics of forest cover is sparse, especially in Ise Forest Reserve. Therefore, this study aimed to assess the changes in land cover in Ise Forest Reserve between 2000 and 2020. Utilizing imagery from Landsat 7 and 8 acquired from the United States Geological Survey (USGS) database, covering the years 2000, 2010, and 2020, we employed a maximum likelihood algorithm to classify the images. Three LULC classes were identified: Forest, Farmland, and Settlement. Our analysis revealed significant shifts in land cover over the studied period. In 2000, forest coverage accounted for 87.5% of the reserve area in 2000, decreasing to 77.46% in 2020. Conversely, farmland increased from 10.74% in 2000 to 17.24% in 2020, while settlement areas expanded from 1.71% to 5.30% during the same period. These changes indicate the impact of anthropogenic activities in the area. In conclusion, LULC changes in Ise forest reserve revealed a concerning trend of deforestation and land cover change due to human activities. This research contributes valuable insights into the evolving landscape dynamics of the reserve, providing essential information for conservation efforts and sustainable land management practices.
Keywords: Change analysis; Deforestation; Land cover; Land use; Maximum Likelihood Algorithm